Construction of Oriented Interconnected BNNS Skeleton by Self‐Growing CNTs Leading High Thermal Conductivity. Issue 6 (21st January 2021) - Li, Xu; Wu, Bin; Li, Ya; Alam, Md Mofasserul; Chen, Peng; Xia, Ru; Lin, Cheng‐Te; Qian, Jiasheng
Abstract: The development of thermal conduction polymer‐based composites is important to solve the heat dissipation of electronic instruments under overheating conditions. The construction of thermal conductive pathways in composites and the reduction of contact resistance between fillers are crucial for concerning excellent thermal conduction properties. Herein, the oriented coherent thermal conductive network in composites is successfully developed via the in situ growth of carbon nanotubes (CNTs) into boron nitride nanosheets (BNNSs) skeleton prepared from ice‐templated. The thermal conductivity of composites reaches 3.21 W m −1 K −1 approximately low filler loading of 9.86 vol%, due to the formation of the covalent bonding between CNTs and BNNSs as reducing the thermal contact resistance by one order of magnitude. More importantly, non‐equilibrium molecular dynamics (NEMD) simulations are carried out to demonstrate the influence of CNTs in elevating the heat conductivity between BNNSs. Meanwhile, the volume resistivity of composites up to 10 15 Ω cm far met the requirement of electrical insulation. This study provided a valuable idea for the design of thermal management materials for potential applications in integrated circuits. Abstract : The construction of a 3D thermal conductive skeleton composed of stacked boron nitride nanosheets connected with in situ grown carbon nanotubes (CNTs) by the combination of ice‐templated and pyrolysis is reported. The composite displays dual functions of high thermal conductivity and electrical insulation.